Preparation method of flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film and its application in microwave absorption
Through the preparation method of flexible magneto-electric dual loss integrated Co3ZnC/Co/BC film, the problem of insufficient absorption performance of existing wave absorbing materials in different frequency ranges is solved, and a broadband and efficient electromagnetic wave absorption effect is achieved.
Patent Information
- Application Number
- CN202410760980.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-06-13
AI Technical Summary
The existing absorbing materials have problems of signal distortion and reducing transmission efficiency during signal transmission. The magnetic loss type materials have poor absorption in the high-frequency band, while the electrical loss type materials have poor absorption performance in the low-frequency band.
Using the preparation method of flexible magneto-electric dual loss integrated Co3ZnC/Co/BC film, the preparation, carbonization and composite of the metal organic frame materials of ZIF-8 and ZIF-67 core-shell structures is formed to form a wave absorbing material with multiple electromagnetic loss mechanisms.
It realizes a wave absorbing material with good broadband wave absorption performance, can effectively absorb electromagnetic waves in various frequency ranges, and has the advantages of being thin, easy to prepare and easy to use.
Smart Images

Figure CN118562167B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a wave absorbing material and application of the wave absorbing material. Background Art
[0002] As a carrier of information transmission, electromagnetic waves have been widely used in radar detection, 5G communications, smart home appliances and other fields, facilitating people's production and life. However, when electromagnetic waves are intertwined during signal transmission, signal distortion and reduced transmission efficiency may occur, which may lead to information leakage and pose a potential threat to national security and human health. Therefore, it is particularly important to effectively absorb excessive electromagnetic radiation and improve information security. As the main component of electromagnetic absorption technology, it is crucial to develop a high-performance absorbing material that meets the above requirements.
[0003] Absorbing materials are mainly divided into magnetic loss materials and electrical loss materials, but both have certain limitations. For example, magnetic loss materials (magnetic metals, ferrites, etc.) have disadvantages such as high density, easy corrosion, easy environmental impact, and poor absorption in high-frequency bands; while electrical loss materials (carbon nanotubes, carbon nanofibers, graphene, ceramics, semiconductors, etc.) have good conductivity and stability, but have poor absorption performance in low-frequency bands, large thickness, and excessive conductivity will lead to impedance matching imbalance. At the same time, most of the existing absorbing materials are powder coating materials, which are difficult to use in practical applications.
[0004] In order to improve and optimize the existing absorbing materials, the present invention will study a flexible magneto-electric double-loss integrated thin-film absorbing device, which will be used in a variety of fields such as aerospace, electronic devices, and medical equipment. Summary of the invention
[0005] The purpose of the present invention is to solve the technical defects of the above-mentioned absorbing materials and provide a flexible magnetic and electric double loss integrated Co 3 Preparation method of ZnC / Co / BC thin film and its application in microwave absorption.
[0006] The present invention provides a flexible magnetic and electric double loss integrated Co 3 Preparation method of ZnC / Co / BC film, flexible magnetoelectric dual-loss integrated Co 3 ZnC / Co / BC thin films have the advantages of microscale structure, light weight, easy preparation, multiple electromagnetic loss mechanisms, wide absorption bandwidth, good wave absorption performance and easy use. They are widely used in electronic devices, communication equipment, medical and other fields.
[0007] A flexible magnetic and electric double loss integrated Co 3 The preparation method of ZnC / Co / BC thin film is specifically prepared according to the following steps:
[0008] 1. Preparation of ZIF-8:
[0009] The zinc salt and dimethylimidazole are dissolved in water, and then reacted at room temperature for a period of time, and then centrifuged, and the solid matter obtained by centrifugation is washed and finally dried to obtain ZIF-8;
[0010] 2. Preparation of ZIF-8@ZIF-67 core-shell structure metal organic framework materials:
[0011] Disperse ZIF-8 in methanol, then add dimethylimidazole, stir magnetically for a period of time, then add cobalt salt and polyvinyl pyrrolidone, stir magnetically for a period of time, centrifuge, wash the solid matter obtained by centrifugation, and finally dry to obtain ZIF-8@ZIF-67 core-shell structure metal organic framework material;
[0012] 3. Carbonization:
[0013] The ZIF-8@ZIF-67 core-shell metal organic framework material was heated to 600℃~900℃ and carbonized at 600℃~900℃ for a period of time to obtain the magnetoelectric double loss core-shell structure Co 3 ZnC / Co powder material;
[0014] 4. Compound:
[0015] The magnetoelectric double loss core-shell structure Co 3 The ZnC / Co powder material was dissolved in water, ultrasonicated for a period of time, and then water-based polyurethane glue and bacterial cellulose were added, stirred for a period of time, and finally filtered to obtain a flexible magnetic and electric double loss integrated Co 3 ZnC / Co / BC thin films.
[0016] A flexible magnetic and electric double loss integrated Co 3 ZnC / Co / BC thin films are used as absorbing materials in electronic devices, communication equipment or medical fields.
[0017] Principles and advantages of the present invention:
[0018] 1. Flexible magnetoelectric dual-loss integrated Co prepared by the present invention 3 The ZnC / Co / BC film has a core-shell structure. The multiple heterogeneous interfaces between different shell layers undergo interface polarization, which leads to the attenuation of electromagnetic waves. At the same time, the core-shell structure causes multiple reflections and scattering of electromagnetic waves inside it, thereby extending the propagation path of electromagnetic waves.
[0019] 2. Co prepared by the present invention 3 ZnC / Co / BC film is a flexible magneto-electric loss-integrated microwave absorption device. 3ZnC@Co is loaded on BC membrane by vacuum filtration, which is simple, environmentally friendly and easy to mass produce;
[0020] 3. Flexible magnetoelectric dual-loss integrated Co prepared by the present invention 3 The ZnC / Co / BC film has good flexibility and exhibits excellent wave-absorbing properties. When the frequency is 14.88 GHz, the minimum reflection loss value reaches -70.0 dB; when the thickness is 2.0 mm, the effective wave-absorbing bandwidth reaches 4.24 GHz. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a physical picture of CCB-2 prepared in Example 2;
[0022] Figure 2 XRD patterns of CCB-1, CCB-2 and CCB-3 prepared in Examples 1 to 3;
[0023] Figure 3 SEM images of CCB-1, CCB-2 and CCB-3 prepared in Examples 1 to 3;
[0024] Figure 4 TEM image of CCB-2 prepared in Example 2;
[0025] Figure 5 The three-dimensional reflection loss graph of CCB-1 prepared in Example 1 and the two-dimensional reflection loss graph of CCB-2 prepared in Example 2 are shown. DETAILED DESCRIPTION
[0026] Specific implementation method 1: This implementation method is a flexible magnetic and electric double loss integrated Co 3 The preparation method of ZnC / Co / BC thin film is specifically prepared according to the following steps:
[0027] 1. Preparation of ZIF-8:
[0028] The zinc salt and dimethylimidazole are dissolved in water, and then reacted at room temperature for a period of time, and then centrifuged, and the solid matter obtained by centrifugation is washed and finally dried to obtain ZIF-8;
[0029] 2. Preparation of ZIF-8@ZIF-67 core-shell structure metal organic framework materials:
[0030] Disperse ZIF-8 in methanol, then add dimethylimidazole, stir magnetically for a period of time, then add cobalt salt and polyvinyl pyrrolidone, stir magnetically for a period of time, centrifuge, wash the solid matter obtained by centrifugation, and finally dry to obtain ZIF-8@ZIF-67 core-shell structure metal organic framework material;
[0031] 3. Carbonization:
[0032] The ZIF-8@ZIF-67 core-shell metal organic framework material was heated to 600℃~900℃ and carbonized at 600℃~900℃ for a period of time to obtain the magnetoelectric double loss core-shell structure Co 3 ZnC / Co powder material;
[0033] 4. Compound:
[0034] The magnetoelectric double loss core-shell structure Co 3 The ZnC / Co powder material was dissolved in water, ultrasonicated for a period of time, and then water-based polyurethane glue and bacterial cellulose were added, stirred for a period of time, and finally filtered to obtain a flexible magnetic and electric double loss integrated Co 3 ZnC / Co / BC thin films.
[0035] Specific embodiment 2: This embodiment differs from the specific embodiment 1 in that the zinc salt described in step 1 is Zn(NO 3 ) 2 6H 2 O、ZnCl 2 or Zn(CHзCOO) 2 ·2H 2 O. The other steps are the same as those in the first specific implementation mode.
[0036] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the mass ratio of the zinc salt described in step 1 to the volume ratio of water is (0.5g-1.2g):(100mL-200mL); the mass ratio of the dimethylimidazole described in step 1 to the volume ratio of water is (3g-4g):(100mL-200mL); the reaction is carried out at room temperature for 15h-24h in step 1. The other steps are the same as those of specific embodiment 1 or 2.
[0037] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the centrifugal speed in step 1 is 5000 rpm to 10000 rpm; deionized water is used to wash the solid matter obtained by centrifugation 3 to 5 times in step 1; the drying temperature in step 1 is 50° C. to 80° C. The other steps are the same as those in specific embodiments 1 to 3.
[0038] Specific embodiment five: This embodiment differs from specific embodiments one to four in that: the mass ratio of ZIF-8 described in step two to the volume ratio of methanol is (0.5g~1.0g):(50mL~100mL); the mass ratio of dimethylimidazole described in step two to the volume ratio of methanol is (4g~5g):(50mL~100mL); the mass ratio of polyvinylpyrrolidone described in step two to the volume ratio of methanol is (500mg~1000mg):(50mL~100mL).
[0039] The other steps are the same as those in Specific Embodiments 1 to 4.
[0040] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the cobalt salt described in step 2 is Co(NO 3 ) 2 6H 2 O or CoCl 2 ; The mass ratio of ZIF-8 to cobalt salt in step 2 is (5-40): (40-85); in step 2, ZIF-8 is dispersed in methanol, and then dimethyl imidazole is added, and magnetic stirring is performed for 5 min-1 h; in step 2, cobalt salt and polyvinyl pyrrolidone are added, and magnetic stirring is performed for 15 h-24 h. The other steps are the same as those in specific embodiments 1 to 5.
[0041] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the centrifugal speed in step 2 is 5000 rpm to 10000 rpm; the solid matter obtained by centrifugation is washed 3 to 5 times with deionized water in step 2; the drying temperature in step 2 is 50° C. to 80° C. The other steps are the same as those in specific embodiments 1 to 6.
[0042] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is that the heating rate described in step three is 5°C / min to 7°C / min; the carbonization time described in step three is 6h to 8h; the magnetoelectric double loss core-shell structure Co in step four 3 The mass ratio of ZnC / Co powder material to water is (0.05g-0.1g):(20mL-30mL); the water-based polyurethane glue described in step 4 is purchased from Shenzhen Yoshida Chemical Co., Ltd.; the volume ratio of the water-based polyurethane glue described in step 4 to water is (1mL-2mL):(15mL-25mL). The other steps are the same as those in specific embodiments 1 to 7.
[0043] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the mass ratio of bacterial cellulose to water in step 4 is (0.1 g to 0.5 g): (15 mL to 25 mL); the ultrasonic time in step 4 is 5 min to 7 min; the stirring reaction time in step 4 is 12 h to 24 h; the filtration time in step 4 is 5 min to 30 min. The other steps are the same as those in specific embodiments 1 to 8.
[0044] Specific embodiment 10: This embodiment is a flexible magnetic and electric double loss integrated Co 3 ZnC / Co / BC thin films are used as absorbing materials in electronic devices, communication equipment or medical fields.
[0045] The following examples are used to verify the beneficial effects of the present invention:
[0046] Example 1: A flexible magnetic and electric double loss integrated Co 3 The preparation method of ZnC / Co / BC thin film is specifically prepared according to the following steps:
[0047] 1. Preparation of ZIF-8:
[0048] The zinc salt and dimethylimidazole were dissolved in water, and then reacted at room temperature for 22 hours, and then centrifuged at a centrifugal speed of 8000 rpm. The solid matter obtained by centrifugation was washed three times with deionized water, and finally dried at 50° C. to obtain ZIF-8;
[0049] The zinc salt described in step 1 is Zn(CHзCOO) 2 ·2H 2 O;
[0050] The mass ratio of the zinc salt described in step 1 to the volume ratio of water is 9g:1000mL;
[0051] The mass ratio of dimethylimidazole described in step 1 to the volume ratio of water is 3g:100mL;
[0052] 2. Preparation of ZIF-8@ZIF-67 core-shell structure metal organic framework materials:
[0053] Disperse ZIF-8 in methanol, then add dimethylimidazole, magnetically stir for 5 minutes, then add cobalt salt and polyvinyl pyrrolidone, magnetically stir for 22 hours, then centrifuge at a centrifugal speed of 8000 rpm, wash the solid matter obtained by centrifugation 3 times, and finally dry at 50°C to obtain ZIF-8@ZIF-67 core-shell structure metal organic framework material;
[0054] The mass ratio of ZIF-8 to methanol described in step 2 is 1 g:100 mL;
[0055] The mass ratio of dimethylimidazole described in step 2 to the volume ratio of methanol is 4g:50mL;
[0056] The mass ratio of polyvinyl pyrrolidone to methanol in step 2 is 10 mg:1 mL;
[0057] The cobalt salt described in step 2 is Co(NO 3 ) 2 6H 2 O;
[0058] The mass ratio of ZIF-8 to cobalt salt described in step 2 is 36:41;
[0059] 3. Carbonization:
[0060] The ZIF-8@ZIF-67 core-shell metal organic framework material was heated to 800°C at a rate of 5°C / min and carbonized at 800°C for 7h to obtain a magnetoelectric dual-loss core-shell structure Co 3 ZnC / Co powder material;
[0061] 4. Compound:
[0062] The magnetoelectric double loss core-shell structure Co 3 The ZnC / Co powder material was dissolved in water, ultrasonicated for 5 minutes, and then water-based polyurethane glue and bacterial cellulose were added. The reaction was stirred for 22 hours and finally filtered for 30 minutes to obtain the flexible magnetic and electric double loss integrated Co 3 ZnC / Co / BC film (CCB-1);
[0063] The magnetoelectric double loss core-shell structure Co described in step 4 3 The mass ratio of ZnC / Co powder material to the volume of water is 1 g:250 mL;
[0064] The water-based polyurethane adhesive described in step 4 was purchased from Shenzhen Yoshida Chemical Co., Ltd.;
[0065] The volume ratio of the water-based polyurethane glue to water in step 4 is 1 mL:20 mL;
[0066] The mass ratio of bacterial cellulose to water described in step 4 is 0.1 g:20 mL.
[0067] Example 2: The difference between this example and Example 1 is that the mass ratio of ZIF-8 to cobalt salt in step 2 is 18:41; the flexible magnetoelectric dual-loss integrated Co 3 The ZnC / Co / BC film is denoted as CCB-2. Other steps and parameters are the same as those in Example 1.
[0068] Example 3: The difference between this example and Example 1 is that the mass ratio of ZIF-8 to cobalt salt in step 2 is 9:41; the flexible magnetoelectric dual-loss integrated Co 3 The ZnC / Co / BC film is denoted as CCB-3. Other steps and parameters are the same as those in Example 1.
[0069] Figure 1 This is a physical picture of CCB-2 prepared in Example 2;
[0070] from Figure 1 It can be seen that the flexible magnetoelectric double loss integrated Co prepared in Example 2 3 ZnC / Co / BC film has good flexibility and adaptability, can maintain its performance when bent or stretched, and has a low density. It has broad application prospects in flexible electronic devices, smart phones, wearable devices and other fields.
[0071] Figure 2 XRD patterns of CCB-1, CCB-2 and CCB-3 prepared in Examples 1 to 3;
[0072] from Figure 2 It can be seen that the diffraction peaks at 44.3°, 51.4° and 75.8° correspond to the (111), (200) and (220) crystal planes of metal Co with a face-centered cubic (FCC) structure (JCPDS No.15-0806). The other three diffraction peaks at 41.9°, 48.7° and 71.5° correspond to Co with a body-centered cubic (BCC) structure. 3 (111), (200) and (220) planes of ZnC (JCPDS No. 29-0524).
[0073] Figure 3 SEM images of CCB-1, CCB-2 and CCB-3 prepared in Examples 1 to 3;
[0074] Figure 4 TEM image of CCB-2 prepared in Example 2;
[0075] Through electron microscope SEM and transmission electron microscope TEM images, Co 3 ZnC / Co / BC structure and morphology; SEM images show that Co 3 ZnC / Co has a rhombic dodecahedral structure and is dispersed in bacterial cellulose BC; TEM shows that Co 3 ZnC / Co is a hollow structure. The carbothermal reduction process reduces metal cations to metal nanoparticles. The reduced Zn particles migrate to the surface of the carrier and combine with Co to generate Co 3 ZnC, Co3 ZnC and Co nanoparticles are dispersed in the carbon shell, and the catalytic effect of Co leads to the production of a large number of carbon nanotubes on the surface.
[0076] Figure 5 A three-dimensional reflection loss graph of CCB-1 prepared in Example 1 and a two-dimensional reflection loss graph of CCB-2 prepared in Example 2;
[0077] from Figure 5 It can be seen that the CCB-1 prepared in Example 1 exhibits excellent wave absorbing performance. When the frequency is 14.88 GHz, the minimum reflection loss value reaches -70.0 dB; when the thickness of the CCB-2 prepared in Example 2 is 2.0 mm, the effective wave absorbing bandwidth reaches 4.24 GHz.
[0078] Flexible magnetoelectric dual-loss integrated Co prepared in Example 1 3 When the frequency of ZnC / Co / BC film (CCB-1) is 14.88GHz, the minimum reflection loss value reaches -70.0dB; when the thickness is 1.92mm, the effective absorption bandwidth reaches 3.92GHz;
[0079] Flexible magnetoelectric dual-loss integrated Co prepared in Example 2 3 When the frequency of ZnC / Co / BC film (CCB-2) is 7.68GHz, the minimum reflection loss value reaches -35.12dB; when the thickness is 2.0mm, the effective absorption bandwidth reaches 4.24GHz;
[0080] Example 3: Flexible magnetoelectric dual-loss integrated Co 3 When the frequency of ZnC / Co / BC film (CCB-3) is 6.64GHz, the minimum reflection loss value reaches 12.88dB; when the thickness is 2.5mm, the effective absorption bandwidth reaches 2GHz.
Claims
1. A method for preparing a flexible magnetoelectric dual-loss integrated Co3ZnC / Co / BC film, characterized in that In the Co3ZnC / Co / BC film, Co3ZnC / Co is a hollow structure of rhombic dodecahedron, which is dispersed in bacterial cellulose BC; The preparation method is specifically prepared according to the following steps:
1. Preparation of ZIF-8: The zinc salt and dimethylimidazole are dissolved in water, and then reacted at room temperature for a period of time, and then centrifuged, and the solid matter obtained by centrifugation is washed and finally dried to obtain ZIF-8; 2. Preparation of ZIF-8@ZIF-67 core-shell structure metal organic framework materials: Disperse ZIF-8 in methanol, then add dimethylimidazole, stir magnetically for a period of time, then add cobalt salt and polyvinyl pyrrolidone, stir magnetically for a period of time, centrifuge, wash the solid matter obtained by centrifugation, and finally dry to obtain ZIF-8@ZIF-67 core-shell structure metal organic framework material; The mass ratio of ZIF-8 to cobalt salt described in step 2 is (5-40):(40-85); 3. Carbonization: The ZIF-8@ZIF-67 core-shell metal organic framework material is heated to 600℃~900℃ and carbonized at 600℃~900℃ for a period of time to obtain a magneto-electric dual-loss core-shell structure Co3ZnC / Co powder material; The heating rate in step 3 is 5°C / min~7°C / min; the carbonization time in step 3 is 6h~8h; 4. Compound: The magnetoelectric double loss core-shell structure Co3ZnC / Co powder material was dissolved in water, ultrasonicated for a period of time, and then water-based polyurethane glue and bacterial cellulose were added, stirred for a period of time, and finally filtered to obtain a flexible magnetoelectric double loss integrated Co3ZnC / Co / BC film; The mass ratio of the magnetoelectric double-loss core-shell structure Co3ZnC / Co powder material described in step 4 to the volume ratio of water is (0.05g~0.1g):(20mL~30mL); The volume ratio of the water-based polyurethane glue to water in step 4 is (1 mL~2 mL):(15 mL~25 mL); The volume ratio of the bacterial cellulose mass to water described in step 4 is (0.1 g ~ 0.5 g): (15 mL ~ 25 mL); The stirring reaction time in step 4 is 12h~24h.
2. The method for preparing a flexible magnetoelectric dual-loss integrated Co3ZnC / Co / BC film according to claim 1, characterized in that The zinc salt described in step 1 is Zn(NO3)2·6H2O, ZnCl2 or Zn(CHзCOO)2·2H2O.
3. The method for preparing a flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film according to claim 1, characterized in that The mass ratio of the zinc salt described in step one to the volume ratio of water is (0.5g~1.2g):(100mL~200mL); the mass ratio of the dimethylimidazole described in step one to the volume ratio of water is (3g~4g):(100mL~200mL); the reaction in step one is carried out at room temperature for 15h~24h.
4. The method for preparing a flexible magnetoelectric dual-loss integrated Co3ZnC / Co / BC film according to claim 1, characterized in that The centrifugal speed in step 1 is 5000 rpm to 10000 rpm; the solid matter obtained by centrifugation is washed 3 to 5 times with deionized water in step 1; the drying temperature in step 1 is 50° C. to 80° C.
5. The method for preparing a flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film according to claim 1, characterized in that The mass ratio of ZIF-8 described in step 2 to the volume ratio of methanol is (0.5g~1.0g):(50mL~100mL); the mass ratio of dimethylimidazole described in step 2 to the volume ratio of methanol is (4g~5g):(50mL~100mL); the mass ratio of polyvinylpyrrolidone described in step 2 to the volume ratio of methanol is (500mg~1000mg):(50mL~100mL).
6. The method for preparing a flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film according to claim 1, characterized in that The cobalt salt described in step 2 is Co(NO3)2 6H2O or CoCl2; in step 2, ZIF-8 is dispersed in methanol, and then dimethylimidazole is added, and magnetic stirring is performed for 5min~60min; in step 2, cobalt salt and polyvinyl pyrrolidone are added, and magnetic stirring is performed for 15h~24h.
7. The method for preparing a flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film according to claim 1, characterized in that The centrifugal speed in step 2 is 5000 rpm to 10000 rpm; the solid matter obtained by centrifugation is washed 3 to 5 times with deionized water in step 2; the drying temperature in step 2 is 50° C. to 80° C.
8. The method for preparing a flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film according to claim 1, characterized in that The ultrasonic time in step 4 is 5 min to 7 min; the filtration time in step 4 is 5 min to 30 min.
9. Application of a flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film prepared by the preparation method according to claim 1, characterized in that A flexible magneto-electric dual-loss integrated Co3ZnC / Co / BC film is used as an absorbing material in electronic devices, communication equipment or medical fields.
Citation Information
Patent Citations
Bacteria cellulose / ferrite composite absorbing material and preparation method thereof
CN103834064A
MOFs derivative material with electromagnetic wave absorption performance and preparation method thereof
CN115716641A
ZIF-8 / BC forming body and preparation method thereof
CN117000193A
Preparation method of core-shell structure TiO2 (at) N / C (at) Co / C composite wave-absorbing agent
CN117921018A